Viscosity, surface tension, and density of binary mixtures of the liquid organic hydrogen carrier diphenylmethane with benzophenone. (26th April 2022) - Kerscher, Manuel; Jander, Julius H.; Cui, Junwei; Martin, Max M.; Wolf, Moritz; Preuster, Patrick; Rausch, Michael H.; Wasserscheid, Peter; Koller, Thomas M.; Fröba, Andreas P.
Abstract: The liquid organic hydrogen carrier (LOHC) diphenylmethane may react to benzophenone in the presence of air, especially at elevated temperatures. Therefore, information about the influence of benzophenone added to diphenylmethane on process-relevant thermophysical properties is required. In the present contribution, the liquid viscosity, surface tension, and liquid density of binary mixtures of diphenylmethane with benzophenone are determined between (283 and 573) K using complementary experimental methods. Investigations on the surface tension by the pendant-drop method and surface light scattering indicate molecular orientation effects of benzophenone at the vapor-liquid interface. With increasing benzophenone content, an increase in density, surface tension, and especially viscosity is found. For the latter property, a distinct change in the temperature dependence is observed at the transition from the liquid to the supercooled liquid state. Furthermore, water dissolved in benzophenone causes changes within 15% and 3% relative to the viscosity and surface tension of benzophenone, respectively. Graphical abstract: Image 1 Highlights: Surface light scattering and conventional methods applied between 283 and 573 K. Surface tension measurements indicate surface orientation effects of benzophenone. Larger density, surface tension, and viscosity with increasing benzophenone content. Big change in temperature dependence of viscosity from liquid to supercooled liquid. Dissolved water has minor impact on viscosity and surface tension of benzophenone.